Developing Picture Storybook in The Human Excretory System Concepts for Improving Students’ Interests Science Learning - Ruqiah Ganda Putri Panjaitan*; Galih Albarra Shidiq; Wulan Muhar Pratiwi; Yokhebed Yokhebed (Universitas Syiah Kuala, 2021)
The excretion system are completely abstractive and complex, so it is desirable a tool that can visualize the excretion process and enable students to understand the modules well. The using of picture storybook is potential to increase the interest and activities of students. The response is a measurable reaction produced by somebody in analyzing an object that can generate an attitude. So, the purpose of this study is to investigate students’ responses to the picture storybook as a part of the teaching material which can facilitate students' thinking. This study involved the seven steps: the introduction, planning, and development of the initial product, initial field trial, revision on the main product, field trial, and revision on the operational product. The field trial was conducted to determine students’ responses to the dimension of cognitive, affective, and conative aspects through exploring three secondary schools around Pontianak, Indonesia. Subjects in this study were students in grade 8 who had been educated with an excretion system with a total number of three students in each school for the initial field trials; while there were 12 students from each school for the main field trials. Instruments used in this study were a validation paper and a student response form. The results of the initial field trial showed the cognitive aspects (84.57%); the affective aspects (89.38%); and the conative aspects (89.46%). The implication of this research was about the possibility to use a picture storybook for increasing students' interests in science learning that we examined by the subject categories